Cucumber resistance to downy mildew (Pseudoperonospora cubensis) in the Non-Black earth zone of the Russian Federation - I. B. Korottseva (Овощи России, 2020)
Relevance. Currently, downy mildew of cucumber (peronosporosis) is the most harmful disease on this crop in the open ground, has an epiphytotic character and causes significant damage to the crop of greens. Material and methods. The research was carried out on selection and collection material of the laboratory of selection and seed production of pumpkin crops in the open and protected ground of the Moscow region. At least 300 collection and selection samples of cucumber were sown in the open and protected ground (Moscow region) every year, for phytopathological evaluation. Their defeat by downy mildew was taken into account on a 5-point scale. Results. Among the varieties of FSBSI FSVC selection, were less affected by this disease: Edinstvo, Electron 2, Vodoley, Vodopad, F1 Debut, F1 Krepish, F1 Brunette, F1 Frant, F1 Krasotka and F1 VNIISSOK 1. The most resistant to peronosporosis were Japanese varieties – Sadao rishu, Jibai, Higan Fushinari, Tropical slicer and others. Some Polish hybrids – Aladyn (SKW 190), Heron (SKW 290) and Parys (SKW 390), also had increased resistance to downy mildew. It should be noted that the varieties Jerelo and Geim from Ukraine; Dutch hybrids – F1 Sequenza, F1 Bejo 1612, F1 Pontia, 85/2292, F1 Donia mix; from the United States – F1 Calypso. In the selection for resistance to downy mildew you can to use varieties created in the Far East, the Crimean experimental breeding station. As a result of the annual assessment of parent forms on a natural infectious background, samples with increased resistance to downy mildew were selected.